Beyond Silence: A Randomized, Parallel-Group Trial Exploring the Impact of Workplace Mental Health Literacy Training with Healthcare Employees. (December 2018) - Moll, Sandra E.; Patten, Scott; Stuart, Heather; MacDermid, Joy C.; Kirsh, Bonnie
Objective: This study sought to evaluate whether a contact-based workplace education program was more effective than standard mental health literacy training in promoting early intervention and support for healthcare employees with mental health issues. Method: A parallel-group, randomised trial was conducted with employees in 2 multi-site Ontario hospitals with the evaluators blinded to the groups. Participants were randomly assigned to 1 of 2 group-based education programs: Beyond Silence (comprising 6 in-person, 2-h sessions plus 5 online sessions co-led by employees who personally experienced mental health issues) or Mental Health First Aid (a standardised 2-day training program led by a trained facilitator). Participants completed baseline, post-group, and 3-mo follow-up surveys to explore perceived changes in mental health knowledge, stigmatized beliefs, and help-seeking/help-outreach behaviours. An intent-to-treat analysis was completed with 192 participants. Differences were assessed using multi-level mixed models accounting for site, group, and repeated measurement. Results: Neither program led to significant increases in help-seeking or help-outreach behaviours. Both programs increased mental health literacy, improved attitudes towards seeking treatment, and decreased stigmatized beliefs, with sustained changes in stigmatized beliefs more prominent in the Beyond Silence group. Conclusion: Beyond Silence, a new contact-based education program customised for healthcare workers was not superior to standard mental health literacy training in improving mental health help-seeking or help-outreach behaviours in the workplace. The only difference was a reduction in stigmatized beliefs over time. Additional research is needed to explore the factors that lead to behaviour change.